2022
DOI: 10.3390/ijerph19084804
|View full text |Cite
|
Sign up to set email alerts
|

Association of Health and Psychological Factors with Academic Achievement and Non-Verbal Intelligence in University Students with Low Academic Performance: The Influence of Sex

Abstract: Academic achievement, measured with the grade point average (GPA), is a stable characteristic that has been associated with many sociodemographic and psychological variables; however, the relation of these variables with GPA has not been totally elucidated. The objective of this study was to perform an association of health, psychological and personal variables with GPA and non-verbal intelligence in low-academic performance population according to sex. We invited health sciences university students who had fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Poor health has a significant impact on student's overall performance and increases the likelihood of academic failure, grade retention, and dropout [ 1 ]. Many studies showed that grade point average (GPA) is associated with numerous physiological and psychological disorders [ 2 , 3 ]. However, few studies have been conducted among college-age students with hypothyroidism, a group that may be at elevated risk for academic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Poor health has a significant impact on student's overall performance and increases the likelihood of academic failure, grade retention, and dropout [ 1 ]. Many studies showed that grade point average (GPA) is associated with numerous physiological and psychological disorders [ 2 , 3 ]. However, few studies have been conducted among college-age students with hypothyroidism, a group that may be at elevated risk for academic difficulties.…”
Section: Introductionmentioning
confidence: 99%